(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
This article is devoted to the issue of teaching Uzbek language in non-traditional ways in foreign language groups of higher education. The place of this science is incomparable in terms of raising young people in the spirit of patriotism, instilling respect and reverence for the state language. In addition, the effectiveness of the application of information technologies, which are improving with the demands of the times, has always been of urgent importance. Taking this into account, the practical importance of the article is determined by the possibility of using the proposed methods not only in the practice of teaching the Uzbek language, but also in educational courses such as methodology, text linguistics, and literature